A stringy glimpse into the black hole horizon - Nissan Itzhaki; Lior Liram (Journal of High Energy Physics, 2018)
Abstract We elaborate on the recent claim [1] that non-perturbative effects in α′, which are at the core of the FZZ duality, render the region just behind the horizon of the SL(2, ℝ) k /U(1) black hole singular already at the classical level (g s = 0). We argue that the 2D classical SL(2, ℝ) k /U(1) black hole could shed some light on quantum black holes in higher dimensions including large black holes in AdS5 × S 5.